2008
DOI: 10.1074/mcp.m800108-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Quantitative Nature of MALDI-TOF MS

Abstract: MALDI-TOF MS has been applied by several groups to relative quantitative measurements. At the same time, the non-quantitative character of this method has been widely reported. We conducted experiments to test the reliability of this technique for quantitation using the statistical method of inverse confidence limit calculation for the first time in this context. The relationship between relative intensities of known amounts of standard peptides and their concentration ratios was investigated. We found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 68 publications
3
118
0
Order By: Relevance
“…It is widely accepted that MALDI-TOF MS is not inherently quantitative, and the direct use of mass intensities for quantification is not practical. 32 However, the calibration curve is linear for target concentrations ranging from 0.05 to 50 mg kg -1 as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that MALDI-TOF MS is not inherently quantitative, and the direct use of mass intensities for quantification is not practical. 32 However, the calibration curve is linear for target concentrations ranging from 0.05 to 50 mg kg -1 as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…It also was found that although the signal intensity of tests performed using CHCA could be increased by adding a precoat of the matrix before sample loading (data for samples where precoating was not performed is not shown), H11 and H21 could be identified and differentiated only by MALDI-TOF using DHB; therefore, it was decided that DHB would be the matrix of choice for MALDI-TOF MS-H. This decision was not impeded by the fact that DHB matrix crystals are clumpy and known to produce hot spots during analysis (23,24), as these manifestations should not affect total signal intensity. Repeated tests summarized in Table 1 indicated that the DHB matrix worked well to identify examined reference strains.…”
Section: Proof-of-principle Testing Of Maldi-tof Ms-hmentioning
confidence: 99%
“…Figure 4a and b show the MALDI spectra of 10 pmol each of Y 5 R and Y 6 , respectively, in 25 nmol of solid CHCA. Because CHCA is a 'hot' matrix [1], most of the [Y 6 + H] + dissociated to immonium Y. Including the abundance of this ion, the total abundance of the analyte-derived ions after normalization to the matrix ion abundance is substantial for both peptides.…”
Section: Ionization Efficiency Solid Versus Liquid Matrixesmentioning
confidence: 99%
“…Tolerance to the presence of contaminants in a sample [4,5] is often cited as an important advantage of MALDI over electrospray ionization, which is another popular ionization technique for biomolecules. In spite of its popularity, MALDI is not regarded as a useful quantitative tool, mainly because the ion signals produced by MALDI display shot-to-shot variation at spots, spot-tospot variation on samples, and sample-to-sample variation [1,6]. In the MALDI of a solid sample composed of an analyte-matrix mixture, sample inhomogeneity is one of the factors responsible for such variations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%